Biofumigation for the management of Sclerotium rolfsii, in vegetable cowpea - Peteti Teja Sri (Department of plant pathology,College of Agriculture, 2020)
The study entitled ‘Biofumigation for the management of Sclerotium rolfsii in vegetable cowpea’ was conducted at College of Agriculture, Vellayani and Integrated Farming System Research Station (IFSRS), Karamana during 2018 - 2020 with the objective to develop an eco-friendly strategy for the management of S. rolfsii, an emerging soil borne fungus of vegetable cowpea using the biofumigation potential of various plants and oil cakes. Six isolates of S. rolfsii were collected from different vegetable cowpea growing tracts. The isolate, Sr1 from var. Gitika (Pathanamthitta district) was identified as the most virulent based on virulence rating viz., days taken for symptom development, lesion length, mycelial growth and sclerotial formation; and was used for further studies. Leaf inoculation of the fungus also produced leaf and stem blight, and wilting indicating that the fungus can also attack leaves besides the collar region. The morphological characters including the presence of mycelial septation, granular cytoplasm and clamp connections as well as the molecular identification based on ITS region of rDNA confirmed the fungus as Sclerotium rolfsii. S. rolfsii is soil borne in nature and hence, the pH and moisture of soil as well as the inoculum level of the fungus will determine the incidence of basal stem rot and blight disease. In vitro studies revealed that soil pH of 6.0 and the soil moisture levels of 35 to 50 per cent were the most ideal levels for the mycelial growth and production of sclerotia of the fungus. Two per cent inoculum multiplied in sand-oats medium was standardised as the inoculum level enough for cent per cent basal stem rot and blight resulting in complete crop loss. The antifungal and biofumigation potentials of plant extracts viz., mustard, cabbage, garlic creeper, castor, cauliflower, onion and garlic bulbs as well as oil cakes namely castor cake, mustard cake and pongamia cake were tested against S. rolfsii by poisoned food technique and paired plate technique respectively. Confined container technique was used to test the inhibition of sclerotia. Among the plant extracts, garlic bulb at one per cent followed by garlic creeper leaves at five per cent completely inhibited the mycelial growth and mycelial regeneration from sclerotia proving its antifungal and biofumigation potentials. Subsequent in vitro studies revealed that garlic bulb at 0.3 per cent and garlic creeper leaves at 2.5 per cent also completely inhibited the mycelial growth and mycelial regeneration from sclerotia. The compatibility of Trichoderma viride (KAU isolate) with garlic bulb and garlic creeper leaf extracts was tested under in vitro conditions. The study revealed that the biocontrol agent was compatible with garlic bulb extract even at 15 per cent and garlic creeper leaves at 20 per cent. A pot culture experiment was conducted to assess the efficacy of selected treatments for the management of the disease in the polyhouse of IFSRS, Karamana in CRD using nine treatments with three replications. Soil application of garlic bulb extract @ 3g per kg soil at two weeks before planting followed by soil plastering with cow dung slurry for two weeks and soil application of 500 g cow dung and neem cake (9:1) enriched T. viride at one month after planting resulted in complete disease management compared to the inoculated control (Disease incidence: 88.89 % and Disease severity: 66.66 %). Soil application of garlic creeper leaves @ 25g per kg soil at two weeks before planting followed by soil plastering with cow dung slurry for two weeks and soil application of 500 g cow dung and neem cake (9:1) enriched T. viride at one month after planting was the next best effective treatment for the management of the disease. Studies on the dynamics of soil fungal population before and after biofumigation revealed its significant reduction. Thus, the present study revealed that basal stem rot and blight disease of vegetable cowpea, an emerging disease can be effectively managed by soil application of garlic bulb extract @ 3g per kg soil at two weeks before planting followed by soil plastering with cow dung slurry for two weeks and soil application of 500 g cow dung and neem cake (9:1) enriched T. viride at one month after planting; which can be used as an ecofriendly management strategy for safe-to-eat vegetable cowpea production.